Forensic Linguistic Analysis of the Construction of Investigation Report of Suspect in Criminal Cases of Insulting the Tolaki Ethnic Group in Southeast Sulawesi - Indah Permata Sari; I Nyoman Kardana; I Nyoman Muliana (CV Wahana Publikasi, 2025)
This study examines the construction of the investigation report (BAP) by using forensic linguistics study. This study employs a qualitative approach to analyze the BAP. The primary data used consist of two copies obtained from the Regional Police Department of Southeast Sulawesi. The results show that total of 26 productive questions and 4 non-productive questions were found. The most dominant type of question used in the interrogation of the criminal case of insulting the Tolaki ethnic group is the productive closed question type, with 15 occurrences, representing approximately 46.6 percent. In addition, there were six types of presuppositions were identified as correlating with all speech events. These include existential presupposition, factual presupposition, lexical presupposition, structural presupposition, non-factual presupposition, and temporal clause presupposition. The most dominant type of presupposition found was structural presupposition, with a total of 13 occurrences. These research findings affirm that forensic linguistics plays a strategic role in evaluating the quality of investigative examinations and the evidentiary strength of the BAP. The analysis of question types and presuppositions demonstrates that language is not merely a means of communication, but a legal instrument that can influence the validity of a suspect’s statements. Accordingly, the application of forensic linguistic principles enables an objective assessment of whether a BAP is produced through examination procedures that are fair, non-misleading, and consistent with legal standards of proof.